Trust or Trickery? A Systematic Review of Greenwashing and Branding - AlQahtani, Fahad Ali (International Review of Management and Marketing, 2025)
This study aims to systematically review the relationship between greenwashing and branding, with a focus on how deceptive environmental claims influence brand trust, perceived authenticity, and consumer behaviour. It seeks to identify key trends, challenges, and opportunities in sustainable branding. A systematic review was conducted, analysing peer-reviewed articles, industry reports, and conference proceedings published between 2012 and 2024. Scopus, the largest citation and abstract database, was utilized. The selected studies addressing greenwashing and branding were further analysed using bibliometric tools. The findings reveal that greenwashing significantly erodes consumer trust and brand reputation, especially when misleading claims are uncovered. Consumer responses vary based on knowledge levels, with some easily persuaded by green claims and others critically evaluating brand messaging. Authenticity and transparency are found to be crucial in fostering sustainable branding and rebuilding consumer trust. This study synthesizes dispersed literature on greenwashing’s impact on branding, offering a consolidated bibliometric analysis that highlights evolving research patterns. It extends understanding by linking consumer scepticism, trust dynamics, and brand authenticity within the sustainability discourse. This review provides original insights by bridging greenwashing and branding literature systematically. It offers a comprehensive synthesis that benefits academics, marketers, and policymakers working to advance ethical and sustainable branding practices.